2021
DOI: 10.22201/ib.20078706e.2021.92.3072
|View full text |Cite
|
Sign up to set email alerts
|

Variación temporal de la abundancia de la comunidad de peces en el delta del río Usumacinta, México

Abstract: Estuaries are dynamics systems, with great spatiotemporal variation in their environmental and biological characteristics. In this study, we analyzed the community attributes such as richness, diversity, evenness, species and trophic guild abundance, of the ichthyofauna in the delta of the Usumacinta River during rain, dry and north wind seasons. A total of 603 individuals belonging to 15 orders, 23 families, 31 genera and 40 species were obtained. Dorosoma petenense, Cathorops aguadulce, Bairdiella ronchus, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In our study, the high proportion of Poeciliidae in the diet of the Mexican Snook in C2 can be explained by their high relative abundance (Aragón‐Flores et al. 2021) and availability for the predators. For instance, one specimen of Mexican Snook from C2 contained 20 poecilids in its stomach (Petén Molly, Shortfin Molly, Spottail Killifish, and Southern Platyfish).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In our study, the high proportion of Poeciliidae in the diet of the Mexican Snook in C2 can be explained by their high relative abundance (Aragón‐Flores et al. 2021) and availability for the predators. For instance, one specimen of Mexican Snook from C2 contained 20 poecilids in its stomach (Petén Molly, Shortfin Molly, Spottail Killifish, and Southern Platyfish).…”
Section: Discussionmentioning
confidence: 53%
“…2019; Aragón‐Flores et al. 2021). During the rainy season, the low‐salinity conditions caused by high riverine discharge and runoff (Barriero‐Güemes and Aguirre‐León 1999; Fuentes‐Yaco et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in abundance are also influenced by changes in the environmental conditions of the system and by seasonal migrations of the species during their life cycles (Arceo-Carranza et al, 2010;Medina-Gómez et al, 2015;Díaz-Ruiz et al, 2018;Aragón-Flores et al, 2021). Other authors such as Azevedo et al (2007) and Arceo-Carranza et al (2010), have reported similar abundance patterns in other coastal systems related to environmental conditions and the seasonal migration of species linked to their life cycles.…”
Section: Discussionmentioning
confidence: 92%